A desiderata for modeling and reasoning with social knowledge - Gallo, Fabio R. (2015)
The ongoing surge in the amount of users that engage in online activities, as well as the expansion of the type of such activities, has recently made it clear that there is a widening gap between current knowledge representation and reasoning tools and the type of knowledge that is essentially up for grabs for whoever is willing (and has the tools) to extract it from social media sites. In this position paper, we propose the concept of Social Knowledge Base (SKB, for short) as an extension of traditional KBs with representation and reasoning capabilities that arise from the singular combination of characteristics that de ne this setting: (i) ontological knowledge, (ii) user preferences, (iii) reasoning under uncertainty, (iv) stream reasoning, and (v) representation of complex social networks. We propose a list of desirable properties|a desiderata|that next-generation KR formalisms for modeling and reasoning with SKBs should enjoy. The treatment is non-technical, focusing on building a road map of the formidable list of problems that must be solved in this complex setting rather than proposing a concrete solution, which would be impossible in a single article. We conclude by proposing some rst steps towards achieving this goal.